2012
DOI: 10.1111/j.1349-7006.2012.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome following imatinib therapy for chronic myelogenous leukemia, with assessment of dosage and blood levels: the JALSG CML202 study

Abstract: A prospective multicenter Phase II study was performed to examine the efficacy and safety of imatinib therapy in newly diagnosed Japanese patients with chronic‐phase CML. Patients were scheduled to receive imatinib 400 mg daily. Plasma imatinib concentrations were measured by liquid chromatography–tandem mass spectrometry. In 481 evaluable patients, estimated 7‐year overall survival (OS) and event‐free survival (EFS) at a median follow‐up of 65 months were 93% and 87%, respectively. Because imatinib dosage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
1
43
1
Order By: Relevance
“…23) In the same report, the estimated cumulative rate of CCyR or MMR during the first 18 months was significantly lower for patients taking the 200 mg daily dose than for patients in the 400 mg or 300 mg groups. 23) Even for patients intolerant of the 300-400 mg dose of imatinib, excessive dose reductions to ≤200 mg imatinib should be avoided, and such patients should be switched to a 2nd generation TKI. 23) A complete molecular response (CMR) is defined as ≤0.0032% of BCR-ABL 1 transcript levels.…”
Section: Imatinib Tdmmentioning
confidence: 74%
See 3 more Smart Citations
“…23) In the same report, the estimated cumulative rate of CCyR or MMR during the first 18 months was significantly lower for patients taking the 200 mg daily dose than for patients in the 400 mg or 300 mg groups. 23) Even for patients intolerant of the 300-400 mg dose of imatinib, excessive dose reductions to ≤200 mg imatinib should be avoided, and such patients should be switched to a 2nd generation TKI. 23) A complete molecular response (CMR) is defined as ≤0.0032% of BCR-ABL 1 transcript levels.…”
Section: Imatinib Tdmmentioning
confidence: 74%
“…According to results from the previous 14 reports, the mean steady-state imatinib C 0 obtained 24 h after taking a 400 mg standard daily dose was 1226 ng/mL, which is greater than the 1000 ng/mL target concentration. [11][12][13][14][15][16][17][18][19][21][22][23][24][25]32) However, patients obtaining an imatinib C 0 above 1000 ng/mL administered the lower dose of 200 mg were very rare.…”
Section: Imatinib Tdmmentioning
confidence: 99%
See 2 more Smart Citations
“…This treatment failure may have been due to the standard dose of dasatinib not being tolerated. Some studies, including ours, reported that the amount of TKI administered in practice was often less than the standard dose [17,18,[35][36][37]. Therefore, tolerability for a standard dose must be considered when selecting a TKI.…”
Section: Discussionmentioning
confidence: 99%